Cellular Communication Propagation at Drone around Building Environment with Single Knife Edge at 10 GHz - Andrita Ceriana Eska (JURNAL INFOTEL, 2021)
The drone communication systems used a cellular network for controlling a drone from a long distance. That communication propagations between drone and base station were analyzed. The drone moved at the track around building environment. That environment used variations in building height. The communication propagation around building environment caused diffraction mechanism. Single knife edge method is used for that diffraction mechanism. The frequency of communication used 10 GHz. That frequency was influenced by atmospheric attenuation. This research was using some variations such as height of drone track location, transmitter power, and AMC (Adaptive Modulation Coding). MCS (Modulation Coding Scheme) was used AMC such as QPSK, 16 QAM, and 64 QAM. Some result was obtained at this research consist of LOS and NLOS distance, SNR, MCS probability, and percentage of drone coverage. NLOS propagation was caused by building height. The SNR value become increase when higher at drone position, such as drone was moving at 20 meters with height of flying drone 80 m and transmitter power 30 dBm obtained SNR 38.21 dBm. That SNR is affected AMC, so a higher SNR value increases AMC. The drone’s coverage 100%, with a height of flying drone 80 meters and transmitter power of 30 dBm. That condition showed more increasing coverage percentage than 64.8% for height of flying drone 20 meters and transmitter power 30 dBm. That result showed that more drone height increased of coverage percentage, probability modulation, and SNR value.